Effects of community performance-based financing on community health workers’ service delivery in Kayanza health district, Burundi - Gervais, Manirakiza; Odongo, Alfred Owino; Maima, Apollo (International Journal Of Community Medicine And Public Health, 2022)
Background: In many low- and middle-income countries, community services are often provided on a volunteer basis. To make their work more effective in the communities, some of them including Burundi adopted community performance-based financing as form of motivation of community health workers (CHWs). The study aimed to demonstrate the relationship between the community performance-based financing and health service delivery by the community health workers. Methods: It was a cross-sectional study using a comparative approach to assess the relationship with the performance-based financing scheme and the community services delivery. We used a stratified random sampling and inferential statistics used chi square and logistic regression. Results: The occupation of CHWs was significantly associated with counselling for early ANC (p=0.002), women attending early ANC and 4 ANC visits (p=0.000). Female were about 3 times likely to refer FP clients for FP methods uptake [p=0.043, CI= (1.030; 7.462), OR=2.773]. Farmers were 11 times as likely to perform this task as CHWs with other functions [p=0.000, CI= (3.890; 32.733), OR=11.284]. The CHWs who received 9 equipment and above [p=0.037, CI= (1.101)]. Conclusions: The community performance-based financing has a significant relationship with the community health workers service delivery and should be enhanced by trainings, formative supervision, and provision of equipment. Occupation was identified as to predict this association. But further studies be conducted to establish other factors that complement the community performance-based financing in community services delivery.